PESAN PENDIDIKAN PERNIKAHAN DALAM Q.S AL-BAQARAH AYAT 187: (Analisis Kesetaraan Hak dan Kewajiban Suami Istri) - Arif Hidayat; Darodjat; Sriyanto (Al-Majaalis : Jurnal Dirasat Islamiyah, 2024)
The teachings contained in the Quran are beneficial for humanity, both in this world and the hereafter. These teachings are conveyed with eloquence and literary excellence, which is one of the primary miracles of the holy scripture. This research aims to explain the equality of rights and responsibilities between spouses as mentioned in Surah Al-Baqarah, verse 187. It emphasizes the importance of fulfilling obligations and respecting the rights of both husbands and wives within Islamic family law as a foundation for building harmonious relationships. The qualitative literature review (library research) approach was used to obtain relevant research findings. The literature examined in this study includes the Quran and commentaries (tafsir) as primary data sources, along with journal articles and books as secondary data sources. The interpretive method employed is the maudhu’i (thematic) approach. The research results indicate that the intended equality is that both spouses simultaneously have the obligation to fulfill each other’s rights. Whether specific rights or those encompassing both husband and wife, they are equally significant. As stated in Surah Al-Baqarah, verse 187, the purpose of clothing is to cover and protect. Therefore, both husband and wife share the same rights and responsibilities, including concealing each other’s flaws, keeping household issues private, covering each other’s shortcomings, maintaining marital privacy, and safeguarding against immoral actions (zina).